A supramolecular red to near-infrared fluorescent probe for the detection of drugs in urine. Issue 40 (28th September 2018) - Aryal, Gyan H.; Hunter, Kenneth W.; Huang, Liming
Abstract : A host–guest complex based on a newly designed and synthesized cationic perylene dye and cucurbit[8]uril exhibits red-NIR emission, high affinity and stability, and large Stokes shift. It can serve as a red-NIR fluorescent displacement probe for the detection of drugs in urine. Abstract : Water-soluble and fluorescent perylene dyesPMI1 andPMI2 with red to near-infrared (red-NIR) emission and a large Stokes shift were designed and synthesized. These dyes were designed to have two binding units (an aromatic perylene-core and a cationic side group) that allowPMI1 andPMI2 to form strong host–guest complexes with cucurbit[8]uril (CB8) through hydrophobic and electrostatic interactions. As a result, the binding constant of the resulting complexes was determined to be in the range of 10 6 M −1 which increased about 2 orders of magnitude compared to the previously reported perylene dye with only one binding unit. The results also revealed that the fluorescence emission ofPMI1 orPMI2 only in aqueous solution is very low due to the aggregation effect. Upon complexation with CB8, the fluorescence intensity increased about 10-fold while the red-NIR emission and the large Stokes shift were preserved. These host–guest complexes can serve as red-NIR fluorescent displacement probes for the detection of CB8 binding guests. The successful detection of addictive drugs in urine was further demonstrated using the host–guest CB8· PMI1 complex and the interference of autofluorescence from the urine sample was successfully eliminated.